THE ACTIVITIES OF INTERNATIONAL ORGANIZATIONS ON THE ENSURING OF A UNIVERSAL ACCESS TO MEDICINE IN THE CONDITIONS OF THE DEVELOPMENT OF MECHANISMS PROTECTING INTELLECTUAL PROPERTY RIGHTS - A. Kh. ABASHIDZE; V. S. MALICHENKO (Московский журнал международного права)
Ensuring universal access to medicines is an important topic of the international agenda and national healthcare police. Access to medicines is determined by systemic interaction of a number of factors, including investment policy issues, intellectualproperty protection, trade processes, and implementation of state guarantees in free medical care. There are clear imbalances in the provision of adequate level of investment in medicines development, acceptable price formation and ensuring a sufficient level of intellectual property rights protection. Effective regulation of these processes requires expanding the scope of cooperation between internationalorganizations and strengthening the mandate of the World Health Organization to form an international agenda in access to medicines, which will take into account the interests of producers and society. The authors, based on the analysis of the specifics of the pharmaceutical industry development and the level of innovative medicines availability in various regions of the world, came to the conclusion that at the current stage, the initiatives implemented by international organizations do not have a proper balance between the interests of the society and pharmaceutical producers. The authors defined that unified standards of intellectual property rights protection can guarantee the possibility for companies to maintain a high level of funding of R&D to recover economic losses due to investments that do not lead to the creation of a market product. The authors also found that international legal documents establish general principles of regulation that determine the need to refer to the most successful practices, implemented at the national level to ensure a balanced approach to stimulate the development of innovations and expand the coverage of the population with the essential drugs.